2012
DOI: 10.1089/apc.2011.0191
|View full text |Cite
|
Sign up to set email alerts
|

Change in Fibrosis Score as a Predictor of Mortality Among HIV-Infected Patients with Viral Hepatitis

Abstract: Noninvasive markers of liver fibrosis, measured at baseline, have been shown to predict liver-related mortality. It remains unknown if a change in the value of the scores over time predicts mortality in patients with HIV and viral hepatitis. In this retrospective study, survival in HIV/hepatitis B virus (HBV; n = 67), HIV/hepatitis C virus (HCV; n = 43), and HIV/HBV/HCV (n = 41) patients was examined using Kaplan-Meier life table analysis. Aspartate aminotransferase (AST)-to-platelet ratio index (APRI) and FIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…We restricted our laboratory results to those obtained in the outpatient setting to mitigate these effects and the large sample size of our cohort likely offset this variability. Despite these limitations, FIB-4 has been shown to predict liver-related outcomes such as hepatic decompensation 26 and death 15,16 and to out-perform liver biopsy in this regard. 15 It is possible that thrombocytopenia due to immune dysregulation or marrow suppression from advanced HIV disease rather than from liver disease resulted in FIB-4 elevation in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We restricted our laboratory results to those obtained in the outpatient setting to mitigate these effects and the large sample size of our cohort likely offset this variability. Despite these limitations, FIB-4 has been shown to predict liver-related outcomes such as hepatic decompensation 26 and death 15,16 and to out-perform liver biopsy in this regard. 15 It is possible that thrombocytopenia due to immune dysregulation or marrow suppression from advanced HIV disease rather than from liver disease resulted in FIB-4 elevation in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…FIB-4 ≥3.25 is a well-validated threshold shown to be predictive not only of advanced fibrosis, but also of liver-related clinical outcomes and overall mortality. 15,16 Accounting for multiple risk factors for fibrosis, we sought to determine the role of HIV disease severity in the progression of liver disease among those with and without viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…AC of APRI was not associated with disease progression in multivariable analysis in this study. Previous studies have also pointed to the limited value of change in APRI in predicting liver disease progression (20,22). FIB-4 contains age (a strong predictive factor of overall survival), AST, ALT, and platelet count; thus, it is considered a more complex and better prognostic indicator than APRI for evaluating the progression of liver-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical disease evolves over time. Jain MK et al and Bambha K et al reported that increases in FIB-4 and APRI were correlated with outcomes in patients co-infected with HIV and viral hepatitis (22,23). Vergniol J et al reported that 3-year changes of noninvasive fibrosis methods have strong prognostic value in CHC patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…The Fibrosis-4 (FIB-4) index, derived from age, liver aminotransferases and platelet count, is more widely available than biopsy, and has been shown to predict liver-related events and death in patients with chronic hepatitis C virus infection (HCV), HIV and HIV/HCV co-infection (912). …”
Section: Introductionmentioning
confidence: 99%